Masih Tingginya Persalinan di Non Fasilitas Kesehatan Setelah Implementasi Penyuluhan Kesehatan Ibu Bersalin di Kampung Cigobang, Desa Karang Tengah - Triswanti Triswanti; Lia Indria Sari; Mukhlisiana Ahmad; Lala Jamilah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Non-health facility deliveries remain a significant maternal health problem in rural areas, increasing the risk of complications for both mothers and newborns. Cigobang Village, Karang Tengah, Babakan Madang District, is one of the areas where home deliveries assisted by non-health personnel are still practiced. This community service activity was conducted through the Village Community Health Development (PKMD) program involving 103 respondents, there were 8 pregnant women (100%) who still planned to give birth at home assisted by non-health personnel. The objective of this activity was to improve community awareness and knowledge regarding safe delivery practices in health facilities. The methods included a community health assessment using questionnaires, maternal health education sessions, and interactive discussions with pregnant women, families, and community health cadres. The results showed that despite the implementation of health education, some pregnant women still planned home deliveries assisted by non-health personnel due to cultural beliefs, accessibility issues, and financial considerations. The PKMD activities contributed to increased community knowledge; however, continuous education and multisectoral collaboration are required to promote safer delivery practices.